Digestibilidade e desempenho em cordeiros alimentados com dietas contendo feno de amoreira - Alves Cirne, Luis Gabriel; Silva Sobrinho, Americo Garcia da [UNESP]; Santana, Valeria Teixeira [UNESP]; Silva, Felipi Ulian [UNESP]; Oliveira, Emanuel Almeida de [UNESP]; Almeida, Fabiana Alves de [UNESP]; Endo, Viviane [UNESP]; Takahashi, Roque [UNESP]; Pinto de Carvalho, Gleidson Giordano; Zeola, Nivea Maria Brancacci Lopes [UNESP] (Univ Estadual Londrina, 2014)
The experiment was conducted to evaluate the intake, the digestibility and the performance of lambs fed with diets containing 0; 12,5 and 25% of mulberry hay in substitution of the concentrate. It was used a total of 24 lambs Ile de France breed, non castrated, average age 60 days and and 15 kg of body weight, confined, distributed in a completely randomized design. Voluntary intake of nutrients was not altered (P>0.05) by different percentages of mulberry hay inclusion in the concentrate, except ether extract which decreased linear (P<0.01). The digestibility of nutrients, days on feeding, daily weight gain and the feed conversion, were also not affected (P>0.05). The partial substitution of the concentrate, based on soybean meal and corn grain, by mulberry hay up to 25% does not compromise the intake, the digestibility of nutrients and the performance of diet of feedlot lambs.
Digestibility and performance of lambs fed with diets containing mulberry hay
Keywords: Alternative feed; feedlot; intake; weight gain